cAMP Signaling Enhances HIV-1 Long Terminal Repeat (LTR)-directed Transcription and Viral Replication in Bone Marrow Progenitor Cells - Anupam Banerjee; Luna Li; Vanessa Pirrone; Fred C Krebs; Brian Wigdahl; Michael R Nonnemacher (SAGE Publishing, 2017)
CD34 + hematopoietic progenitor cells have been shown to be susceptible to HIV-1 infection, possibly due to a low-level expression of CXCR4, a coreceptor for HIV-1 entry. Given these observations, we have explored the impact of forskolin on cell surface expression of CXCR4 in a cell line model (TF-1). The elevation of intracellular cyclic adenosine monophosphate (cAMP) by forskolin through adenylyl cyclase (AC) resulted in transcriptional upregulation of CXCR4 with a concomitant increase in replication of the CXCR4-utilizing HIV-1 strain IIIB. Transient expression analyses also demonstrated an increase in CXCR4-, CCR5-, and CXCR4-/CCR5-utilizing HIV-1 (LAI, YU2, and 89.6, respectively) promoter activity. Studies also implicated the protein kinase A (PKA) pathway and the downstream transcription factor CREB-1 in interfacing with cAMP response elements located in the CXCR4 and viral promoter. These observations suggest that the cAMP signaling pathway may serve as a regulator of CXCR4 levels and concomitantly of HIV-1 replication in bone marrow (BM) progenitor cells.